Assessment of genetic uniformity in micro propagated plantlets of turmeric (Curcuma longa L.) through DNA markers - Gowda, M. R. Swamy; Sowmya, R. (Current Botany, 2024)
Turmeric is herbaceous plant, characterized by long lance-shaped leaves sprouting from its rhizomatous underground stem. Notably, its rhizomes contain the bioactive compounds curcuminoids, renowned for its medicinal and culinary significance. However, meeting the surging demand for turmeric, particularly during off- seasons, presents a formidable challenge due to the sluggish vegetative propagation rate in Curcuma longa. Given the scarcity of sexual reproduction in turmeric, micropropagation emerges as the convenient method for obtaining disease-free seeds. In addressing the challenge of direct regeneration of the native Erode local cultivar of turmeric, this study endeavors to establish a protocol for in vitro plantlet production. Results indicate that multiple shoots were successfully induced, notably with 13.32 μM of 6-benzylaminopurine (BAP), yielding a response rate of 73.2±4.7% and an average shoot count of 6.95±0.81 per explant. Subsequently, a concentration of 17.76 μM of BAP demonstrated a response rate of 56.5%±4.7%, with an average shoot count of 5.94±0.81 per explant. Additionally, a combination of 13.32 μM BAP and 2.68 μM Naphthaleneacetic acid (NAA) resulted in 8.65±0.47 shoots per explant, with a response rate of 73.66±1.25%. Similarly, 13.32 μM BAP combined with 5.37 μM NAA yielded 7.32±0.47 shoots per explant, with a response rate of 72.33±0.47%. The acclimatization of plantlets in a greenhouse exhibited a remarkable survival rate, ranging from 90% to 98%. Importantly, all regenerated plantlets closely resembled the mother plants morphologically. Genetic uniformity assessment, employing 10 ISSR and 4 DAMD markers, indicated more than 90% uniformity among one mother plant and regenerants. This indicates a significant genetic uniformity, ensuring consistency in desired traits across the regenerated plantlets.